Soft Masculinity as Represented in Siwon Choi's Instagram and Twitter Post - Dewi, Windy Meiliyanti Puspita; Kurniati, Nurul Adha (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
The term soft masculinity began to be known as a characteristic of K-Pop since the Korean wave became global. It has three prominent characteristics, such as tender charisma, purity, and politeness. This study aims to analyze how does Siwon Choi represent the character of soft masculinity through his Instagram and Twitter posts. Social semiotic by Kress and Van Leeuwen were used to analyze the visual text and Systemic Functional Linguistic by M.A.K Halliday were used to analyze the written text. Purposeful sampling was deployed to select six photos during 2018-2020. The result of this study found in five photos from Twitter and one photo from Instagram of Siwon Choi’s account represents the character of soft masculinity through the activities in his daily life. This soft masculinity character has become a part of Korean culture nowadays, shifting the traditional masculinity character that tough into the softer ones.